Philippines Country Procurement Assessment Report 2012 - Asian Development Bank (Manila, 2014)
Proper public procurement practices directly reflect good governance. Transparent and effective procurement practices minimize expenditure and create opportunity. Procurement is an enormous component in the process by which governments build infrastructure, such as schools and hospitals. It involves the management of significant amounts of money and is therefore often the cause for allegations of corruption and government inefficiency. The difference between getting public procurement right and doing it wrong has the potential to be either highly rewarding, or highly damaging. In some nations, reforms implemented to improve the efficiency of public procurement have resulted in savings of 1% of a country's gross domestic product. One can see why public procurement is so significant to the development of a country and its people. Citizens have the right to expect their government to spend these funds for the good of the people. In the past, corruption, inefficiency, ignorance, and disorganization have resulted in billions of pesos worth of losses. It is with the importance of these issues in mind that this report is produced to report on the state of procurement in the Philippines today. A 2012 CPAR action plan integrating all the existing and proposed initiatives and recommendations to address the areas for improvement in the Public Procurement System is presented at the end of this report. The action plan provides the road map and agenda for procurement reforms to be undertaken by the government, together with its development partners during 2013-2016. Some of the priorities focus on strengthening monitoring and enforcement and procurement capacity, and improving procurement processes and practices, i.e., (i) implementation of the professionalization program, (ii) implementation of the Agency Procurement Compliance and Performance Indicator, or APCPI and development of mechanisms to enforce compliance, (iii) review and possible revision of the IRR to provide procedures for international competitive bidding, (iv) establishment of an independent complaints or protest review body and development of its governing rules and procedures, and (v) development and implementation of a framework to sustain and ensure CSO participation in procurement monitoring. The Philippine development forum sub-working Group on Procurement will continue to monitor the implementation of the action plan, ensure the availability of funding support and address issues that may arise during implementation.